2023
DOI: 10.1001/jamanetworkopen.2023.2977
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence, Mental Health Symptoms, and Modifiable Health Factors in Women During the COVID-19 Pandemic in the US

Abstract: ImportanceDuring the COVID-19 pandemic, the prevalence and severity of intimate partner violence (IPV) increased. Associations between IPV and mental health symptoms and modifiable health factors early in the pandemic have yet to be explored.ObjectiveTo prospectively investigate the association of IPV with greater risk of mental health symptoms and adverse health factors during the COVID-19 pandemic in 3 cohorts of female participants.Design, Setting, and ParticipantsThis cohort study used observational data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Studies in Belgium have shown that victims of violence are more likely to be dissatisfied with their social interactions, and their weak social support and low trust in health services may lead to more incidents of violence during the pandemic ( 31 ). In the United States, a social survey of 13,597 female participants found that IPV experience was associated with poorer sleep quality, shorter sleep duration, and increased alcohol consumption, and that IPV experience at the onset of the pandemic was associated with more severe mental health symptoms and modifiable health factors in female participants under the age of 60 ( 9 ). IPV is significantly associated with unemployment, women who do not work and whose partners do not work have higher levels of emotional violence during the pandemic in Turkey ( 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Belgium have shown that victims of violence are more likely to be dissatisfied with their social interactions, and their weak social support and low trust in health services may lead to more incidents of violence during the pandemic ( 31 ). In the United States, a social survey of 13,597 female participants found that IPV experience was associated with poorer sleep quality, shorter sleep duration, and increased alcohol consumption, and that IPV experience at the onset of the pandemic was associated with more severe mental health symptoms and modifiable health factors in female participants under the age of 60 ( 9 ). IPV is significantly associated with unemployment, women who do not work and whose partners do not work have higher levels of emotional violence during the pandemic in Turkey ( 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this study found that gender-based violence often results in anxiety and depression among women and girls. These mental health issues have become even more prevalent across the world during the COVID-19 pandemic [36,[48][49][50][51]. Therefore, taking action and focusing on promoting wellness outcomes is essential.…”
Section: Discussionmentioning
confidence: 99%
“…( 15 19 ). Recent research in a large sample of women (N = 13,597) demonstrated that IPV during the COVID-19 pandemic was associated with a 17% increase in using substances to cope with stress ( 20 ). It is also well established that IPV exposure often occurs in the context of substance use, and thus substance use is a modifiable risk factor for IPV ( 21 , 22 ).…”
Section: Identifying Best Practices For Substance-related Intimate Pa...mentioning
confidence: 99%
“…Individuals who survive IPV may use substances to selfmedicate the consequences of IPV (e.g., pain, depressive symptoms, trauma symptoms, etc.) (15)(16)(17)(18)(19). Recent research in a large sample of women (N = 13,597) demonstrated that IPV during the COVID-19 pandemic was associated with a 17% increase in using substances to cope with stress (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation